The Parable of the Storm: Instruction and Demonstration in Mark 4:1–41 - Milinovich, Timothy (Biblical theology bulletin, 2015)
Many analyses of Mark 1–4 sharply separate the Parables discourse (4:1–34) from the Storm pericope (4:35–41) and consider the latter to begin a new phase in Jesus’ ministry (4:35–8:26). However, even scholars who make this distinction note a close link between the Parables and the Storm. In this article I use a narrative-critical approach to identify and engage thirteen lexical connections and how they develop for the implied audience through the narrative structure of 4:1–41. Overall, I seek to demonstrate that the Parables discourse and Storm pericope complement one another and follow the instruction-demonstration pattern evident in 1:21–28; 1:35–45; 2:1–12; 2:13–3:6. In each case, a miraculous demonstration follows an episode of Jesus instruction, the two are marked by a similar setting and lexical connections, and the latter miracle story develops the teaching of the kingdom and divine Sonship of Christ that were initially explained in the adjacent instruction. I will show how Mark 4:1–41 shares this structure and that analyzing the implied audience's reception of the narrative offers new developments of the Parables discourse, explains several obscurities in the Storm pericope, and further demonstrates the theological perspective and narrative line of thought in the text of Mark 1–4.